Color and flexural properties of nanoparticles-modified denture base resin: An in vitro comparative study - Emam, Abdel-Naser M.; Ibrahim Ahmed, Karim-Eldin; Shaaban, Adel M.; Alqhtani, Mohammad Abdullah; Gad, Mohammed M.; Helal, Mohamed Ahmed (International Journal of Health Sciences, 2024)
Objectives: Reinforcement of polymethylmethacrylate (PMMA) denture base resins (DBRs) with inorganic fillers with superior properties and accepted aesthetics are favored and still a big dilemma. This study was undertaken to evaluate the color change, flexural strength, and modulus of elasticity of heat-polymerized DBR material modified with silver nanoparticles (AgNPs) and zirconium dioxide nanoparticles (ZNPs). Methods: Sixty acrylic specimens (30/color test, 30/flexural properties) were fabricated and divided according to nanoparticles type and addition into 3 groups (n = 10). Group-I; unmodified specimens, Group-II; modified specimens with 0.5wt% AgNPs (PMMA/AgNPs), and Group-III; modified specimens with 7.5wt% ZNPs (PMMA/ZNPs). Disc-shape (20 × 3 mm) and bar-shape (65 × 10 × 2.5 mm) specimens were fabricated for color and flexural properties, respectively. The spectrophotometer was used for evaluation of the color change (ΔE). The flexural strength and elastic modulus evaluation was carried out using a 3-point bending test (5 mm/min). Tukey’s post hoc and one-way ANOVA were used to analyze the data at a significant level P ≤ 0.05. Results: PMMA/AgNPs group exhibited a significant increase in color change when compared with PMMA/ZNPs. PMMA/ZNPs showed significantly the highest flexural strength value when compared with unmodified and PMMA/AgNPs groups (P < 0.001), however, there was an absence of significant differences in terms of flexural strength values between PMMA/AgNPs and unmodified groups (P > 0.05). PMMA/AgNPs insignificantly increased its modulus of elasticity strength (P = 0.09410) while PMMA/ZNPs significantly increased its modulus of elasticity strength (P = 0.00396). Conclusion: The AgNPs and ZNPs addition to PMMA increased the color change and AgNPs change the color of DBRs. The flexural attributes of DBRs have been increased by ZNPs.